Macroscopie Studies of Platelet Aggregation. Nature of an Aggregating Factor in Red Blood Cells and Platelets - Øllgaard, E (Thrombosis and Haemostasis, 1961)
In in-vitro experiments, it has been shown that red blood cells and platelets contain a factor which, on addition to a sample of platelet-containing plasma and subsequent rocking of the test tube, causes an aggregation of the platelets which is visible to the naked eye. In equal volumes, the concentration of this factor has been found to be about 5 times as high in platelets as in red cells. The factor is thermostabile, non-protein in nature, and exerts its action independently of the process of coagulation. It is assumed to be carbohydrate in nature. White cells and, to a less degree, plasma and serum seem to be able to destroy the aggregating factor by an enzymatic process.The aggregation is reversible, since white cells as well as certain enzyme poisons and Na+ can reverse the process without any apparent change in the appearance of the platelets. The process observed thus actually seems to be a form of aggregation.